2005
DOI: 10.1111/j.1445-2197.2005.03517.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychological impact and cosmetic outcome of surgical breast cancer strategies

Abstract: While little difference was seen on quality of life assessment, body image is improved with the use of breast conservation and reconstruction. The high satisfaction and cosmesis scores in the breast reconstruction group are an indication of the superior results that can be achieved with breast reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
1
7

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(91 citation statements)
references
References 45 publications
3
80
1
7
Order By: Relevance
“…There was no difference between the two groups with regard to scores for overall health, physical, psychological and social function, and for symptoms. This result is in keeping with those from other studies (15;16), notably the study conducted by Nano et al (17), which showed the absence of any difference in quality of life but better body image in patients undergoing conservative treatments and reconstructions compared to that in patients who had mastectomy without reconstruction. The fact that the effect of reconstruction is restricted to improved body image has many factors.…”
Section: Evaluation Of Body Image and Of Quality Of Lifesupporting
confidence: 82%
“…There was no difference between the two groups with regard to scores for overall health, physical, psychological and social function, and for symptoms. This result is in keeping with those from other studies (15;16), notably the study conducted by Nano et al (17), which showed the absence of any difference in quality of life but better body image in patients undergoing conservative treatments and reconstructions compared to that in patients who had mastectomy without reconstruction. The fact that the effect of reconstruction is restricted to improved body image has many factors.…”
Section: Evaluation Of Body Image and Of Quality Of Lifesupporting
confidence: 82%
“…Previous studies have investigated the influence of cosmetic outcome on psychosocial morbidity in primary breast cancer [6,20]. These studies reported a good correlation between satisfaction with cosmetic outcomes and positive body image perception, sexuality and self-esteem and showed that the more conservative was breast surgery the better were quality of life and psychological adjustment.…”
Section: Discussionmentioning
confidence: 82%
“…Skin sparing mastectomies (SSMs) and immediate breast reconstruction (IBR) preserves the natural contours by sparing the native skin, preserves sensation, minimises scars, gives cosmetic results (thereby increasing self esteem) and lowers psychological morbidity. 1 Oncological safety in terms of local and systemic recurrence is a serious concern.…”
mentioning
confidence: 99%